Death Due to Tianeptine Injection Through Inguinal Incision: Two Case Reports - Ketenci, Hüseyin Çetin; Çakır, Emel; Beyhun, Nazım Ercüment; Boz, Halil; Okumuş, Hasan; Cingöz, Gökhan; Şam, Bülent (The Bulletin of Legal Medicine, 2018)
In recent years, drug use has come to the forefront as one of the most important problems of public health. Tianeptine is an antidepressant that is structurally similar to tricyclic antidepressants and is used for the treatment of depression but is also abused because its pleasing feature has been recognized by drug users. Two forensic cases were autopsied with an interval of 25 days. One case had unilateral unusual inguinal lesions. The other case bilateral unusual inguinal lesions. It was understood that these lesions were preformed, improved surgical catheter incisions in order to facilitate intravenous injections for drug abuse. This application, which was detected in the inguinal region, was found to be interesting. It is aimed to raise the awareness of this application, which is not found in the literature. As a result of the intense human transit, substance abuse habits and methods have also been transferred to citizens...
Keywords: Tianeptine; Autopsy; Inguinal incision; Injection